A study on effects of service quality dimension towards customer satisfaction in Z Rich Corporation Sdn Bhd / Afiqah Izzati Osman - Osman, Afiqah Izzati (Faculty of Business and Management, 2015)
The purpose of this study is to identify the effect of service quality dimension (SERVQUAL model) towards customer satisfaction in Z Rich Corporation, The five dimension of SERVQUAL have been influence on customer satisfaction. The five dimension are tangible, reliability, responsiveness, assurance and empathy as the independent variables while for the dependent variable is customer satisfaction. This research have been improved by questionnaire for the purpose of data collection and distributing it to 100 respondent and the questionnaire were filled up by the customers who come to Z Rich showroom and also customer who already purchased the product before.